The oxidation and thermal stability of two-dimensional transition metal carbides and/or carbonitrides (MXenes) and the improvement based on their surface state. Issue 9 (25th March 2021) - Zheng, Zixiang; Guo, Chunyu; Wang, Enhui; He, Zhijun; Liang, Tongxiang; Yang, Tao; Hou, Xinmei
Abstract : This work provides a comprehensive review focusing on the current research on the stability of MXenes and the methods to improve their stability. Abstract : In recent years, a new family of two-dimensional (2D) transition metal carbides and/or carbonitrides labeled MXenes have greatly attracted worldwide attention. Due to their unique structure and excellent properties, such as unusual hydrophilicity, electrical conductivity, flexibility, and pseudo-capacitance, MXenes have great potential applications in energy storage, water desalination, catalysis, electromagnetic interference shielding, transparent conductive films and so on. However, MXenes exhibit poor stability especially under oxygen-containing conditions because of the structural defects, active transition metals and termination groups, which restrain their application fields. In this review, we focus on the current research on the stability of MXenes including oxidation and thermal stability under various conditions. The mechanism is also discussed. Based on this, the methods to improve the stability of MXenes are proposed, aiming to expand the application scope. Firstly, the structure and synthesis methods of MXenes are briefly introduced. Secondly, the oxidation process and mechanism of MXenes in different environments are introduced, including gaseous, liquid, solid, UV irradiation, hydrothermal, anodic oxidation and so on. Thirdly, the thermal stability of MXenes under an oxygen-containing atmosphere, neutral atmosphere or reducing atmosphere at different temperatures is also introduced. Finally, the methods of improving the stability of MXenes including controlling the storage environment, improving the synthesis method, regulating functional terminations, chemical edge capping methods and physical packaging methods are further discussed.